2021
DOI: 10.1177/2515690x211006332
|View full text |Cite
|
Sign up to set email alerts
|

National Internet-Based Survey of the Use, Barriers, Reasons and Beliefs of Mind-Body Practices During the Early Months of the COVID-19 Pandemic

Abstract: The purpose of this study was to learn about the use, barriers, reasons and beliefs regarding mind-body practices among adults living in the United States during the beginning months of the 2019 novel coronavirus disease (COVID-19) pandemic. An on-line survey was developed following the Checklist for Reporting Results of Internet e-Surveys (CHERRIES) guidelines and using the online survey software program, Qualtrics® XM, platform. Pilot testing of the survey was conducted for usability and functionality. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Twenty-two studies were conducted in China ( 27 , 31 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 65 , 67 , 69 73 , 75 77 ), six in Saudi Arabia ( 18 , 21 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-two studies were conducted in China ( 27 , 31 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 65 , 67 , 69 73 , 75 77 ), six in Saudi Arabia ( 18 , 21 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 65 , 67 , 69 73 , 75 77 ), functional food (supplements) or herbs ( n = 20) ( 17 24 , 29 , 36 , 38 , 43 , 49 52 , 57 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already shown that mind–body practices, such as yoga and meditation have beneficial effects on mental health and reduce stress in different populations and circumstances [ 47 51 ]. A study performed in the early months of the COVID-19 pandemic, reported an increased use of mind–body practices with promoting health, reducing stress and relaxation reported as the three most important reasons [ 52 ]. As we found that worries to get infected was an important predictive factor for the use of all CM modalities and 74.6% of the respondents indicated to use self-help techniques including yoga and meditation to promote general well-being, this implies that reducing stress and psychological concerns with respect to COVID-19 could play a role.…”
Section: Discussionmentioning
confidence: 99%